Expression of Functional Coagulation Factor XIII in Escherichia coli - Board, P G; Pierce, K; Coggan, M (Thrombosis and Haemostasis, 1990)
Coagulation factor XIII is a zymogen that can be activated by thrombin cleavage to a transglutaminase that catalyses the formation of covalent crosslinks between fibrin chains in the final stages of the blood clotting cascade. Although circulating factor-XIII is composed of A and B subunits the catalytic activity is a property of the A subunits. In this study we have constructed a plasmid (pKKF13A) that contains a cDNA encoding the A subunit positioned downstream of a tac promoter. Escherichia coli containing this plasmid produce A subunit protein when grown in the presence of IPTG. The cloned A subunit has been partially purified and characterized. Comparison with A subunits purified from plasma showed that the cloned A subunits were of the same size, assembled as dimers, and had the same native electrophoretic mobility. The cloned A subunits expressed transglutaminase activity with putrescine, dansylcadaverine and casein as substrates, and were able to crosslink fibrin in clots formed from A subunit deficient plasma. These studies have demonstrated that functional recombinant factor XIII A subunit can be produced in E. coli and suggest that recombinant factor XIII can potentially provide a safe and inexhaustible supply for therapeutic use.